Constructing acid-resistant chitosan/cellulose nanofibrils composite membrane for the adsorption of methylene blue. Issue 3 (June 2022) - Wu, Jianming; Dong, Zihui; Li, Xiuping; Li, Peng; Wei, Jiedong; Hu, Mei; Geng, Lihong; Peng, Xiangfang
Abstract: Facing the serious environmental problem caused by water pollution, it is still challenging to develop a kind of acidic wastewater treatment adsorbent with high adsorption efficiency. In this study, the negative charged cellulose nanofibrils (CNF) were used to enhance the acid-resistance of the positive charged chitosan (CTS) via both ionic and hydrogen-bonding crosslinking interactions. The prepared CTS/CNF composite membrane presented an excellent acid-resistant property (approximately 95% acid-resistant degree) and 14.71 mg/g of adsorption capacity for methylene blue in the strong acidic environment (pH = 1.22), surpassing almost reported adsorbents. Besides, the adsorption process for methylene blue conformed to the pseudo-first-order kinetic model and the Langmuir isotherm model better. Furthermore, the obtained CTS/CNF composite membrane presented excellent recyclability (about 85% desorption rate) after five recycles of adsorption-desorption. Consequently, as a novel and efficient adsorbent, the CTS/CNF composite membrane showed an outstanding application potential in the treatment of acidic wastewater. Graphical Abstract: ga1 Highlights: Enhance the acid-resistance via ionic and hydrogen-bonding crosslinking interactions. Membrane adsorption comes from hydrogen-bond and electrostatic-force interactions. Adsorption occurs via pseudo-first-order kinetic and Langmuir isotherm models. The composite membrane can be regenerated easily in acidic wastewater treatment.